2020
DOI: 10.1044/2020_aja-19-00039
|View full text |Cite
|
Sign up to set email alerts
|

Media Use by Older Adults With Hearing Loss: An Exploratory Survey

Abstract: Objectives There has been a substantial increase in people with health conditions seeking health-related information online. The aim of this study was to examine the media usage by older adults with hearing loss. Method The study used a cross-sectional survey design. A total of 556 older adults with hearing loss (Hearing Tracker website users) completed the survey that was focused on (a) demographic information, (b) general electronic media usage, (c) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…This may have played a crucial role in determining the understandability and actionability scores of these materials that are freely available to public. Overall, these results indicate that there is need for significant improvement in the video quality and content in order to facilitate behavior change in individuals with hearing 21 loss who may be watching these videos as source of information for their decision-making (Manchaiah et al, 2020a).…”
Section: Understandability and Actionability Of Youtube Videos Pertaimentioning
confidence: 85%
See 1 more Smart Citation
“…This may have played a crucial role in determining the understandability and actionability scores of these materials that are freely available to public. Overall, these results indicate that there is need for significant improvement in the video quality and content in order to facilitate behavior change in individuals with hearing 21 loss who may be watching these videos as source of information for their decision-making (Manchaiah et al, 2020a).…”
Section: Understandability and Actionability Of Youtube Videos Pertaimentioning
confidence: 85%
“…It is also a common outlet for health-related information to be shared by professionals, health organizations, and/or patients and facilitates user interactions through commenting, responding, and messaging options (Duke et al, 2019;Wong et al, 2016). A recent study that examined the media usage by older adults with hearing loss suggested that YouTube was the most frequently used social media platform, although nearly half of the study participants reported that they find it extremely hard to find hearing health information in YouTube videos (Manchaiah et al, 2020a). Content analysis of YouTube information has repeatedly indicated variable unregulated quality for numerous health care concerns, including diabetes and infection preventing.…”
Section: Introductionmentioning
confidence: 99%
“…A study looking at media representation of tinnitus in newspapers and the media in the United States identified greater coverage of these such as diagnosis and cause, symptoms, social support, research and development, challenges, symptoms and coping 28 . Efforts are needed to both examine and improve access to tinnitus and hearing‐related health information in European languages, especially via electronic media (eg, social media) from which many users are likely to gather hearing health information 29 …”
Section: Discussionmentioning
confidence: 99%
“…28 Efforts are needed to both examine and improve access to tinnitus and hearing-related health information in European languages, especially via electronic media (eg, social media) from which many users are likely to gather hearing health information. 29 Tinnitus support groups are often a valuable resource to those with tinnitus as they provide social connectedness and shared social identification. 30 Considering this, it was interesting that the majority of respondents (82%) reported not attending a support group prior to the pandemic and very few attended an online tinnitus support group during the pandemic.…”
Section: F I G U R E 3 Overview Of the Suggestions For Developing Tinnitus Care See Table 2 For An Explanation Of These Categoriesmentioning
confidence: 99%
See 1 more Smart Citation